Risk Based Supervision - Randle, Tony (World Bank, Washington, DC, 2017)
The role of supervisory authorities undertaking prudential supervision is to promote the maintenance of efficient, fair, safe and stable insurance markets for the benefit and protection of policyholders. An effective supervisory authority is able to require an insurer to take timely preventive and corrective measures if the insurer fails to operate in a manner that is consistent with sound business practices or regulatory requirements. Traditionally, authorities have performed this role by way of compliance based supervision. Under this style of supervision, insurers must comply with a set of prudential rules generally written into the law or the subordinate legislation. The role of the supervisory authority is to ensure that insurers do, in fact, comply with these rules. In recent years, supervision has been evolving and moving from a style that is compliance based to one that is risk based. This progression has also been a feature of the activities of bank supervision and pension supervision.